Konsep Belajar dalam Teori Konstruktivistik dan Islam Klasik (Komparasi Pemikiran Bobbi De Porter dan Al-Ghazali) - Siti Ma'rifatul Hasanah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2017)
Teaching learning is the key success in education. Learning have a major role in salvaging the culture from generation to generation. It is needed a theory of learning to continue the cultural heritage and educate the young generation to be able to carry on that role. The importance of teaching and learning got the attention of Western psychologists, so at the beginning of the 19th century came the theories of learning and instruction. The main purpose of this paper is to find out which aspects of the similarities and differences of the two theories are related to the study. The results show that there were differences and some similarities between the constructivism learning theory from Bobbi DePorter and the classical Islamic learning theory from Al-Ghazali. Both of theories aims to make teaching learning is effective, maximum and without burdening. Spiritual aspects in the classical Islamic learning theory are discussed using psychology, sociology and neurology approaches of constructivism learning theory. One aspect that makes the Islamic learning theory more superior is the cultivation of the moral education in all aspects, and the learning objectives for lasting happiness, in this world and hereafter.